Nursing Students’ Perceptions about the Effects of Climate Change on Health: A Descriptive Exploratory Study - Jonalyn P. Santos; Eladio Martin S. Gumabay (Nurse Media: Journal of Nursing, 2024)
Background: Climate change is recognized as an important health concern that the health sector and nurses must prepare for. Adequate preparation and understanding of its effects on health must be exemplified by nurses and nursing students. Previous studies showed that nurses and nursing students have good knowledge of climate change and its effects on health. However, none of these studies were conducted in the Philippines.